A meta-analysis of the effects of the 5-hydroxytryptamine transporter gene-linked promoter region polymorphism on susceptibility to lifelong premature ejaculation. - Lijie Zhu; Yuanyuan Mi; Xiaoming You; Sheng Wu; Hongbao Shao; Feng Dai; Tao Peng; Feng Qin; Ninghan Feng (PLoS ONE, 2013)
OBJECTIVE: Premature ejaculation (PE) has been reported as the most common male sexual dysfunction with global prevalence rates estimated at approximately 30%. The neurobiogenesis of ejaculation is very complex and involves the serotoninergic (5-hydroxytryptamine, 5-HT) system. Recently, genetic polymorphisms located on SLC6A4 gene codifying for 5-HT transporter (5-HTT), the major regulator of serotonic neurotransmission, have been linked with the pathogenesis and risk of PE. Apparently studies of this type of polymorphism in PE have show conflicting results. METHODS: A meta-analysis was performed that are available in relation with 5-HTT gene-linked promoter region (5-HTTLPR) polymorphism and the risk of lifelong PE (LPE) in men to clarify this relationship. We searched Pubmed and Embase (last search updated on Aug 2012) using 'premature ejaculation', 'polymorphism or variant', 'genotype', 'ejaculatory function', and 'rapid ejaculation' as keywords and reference lists of studies corresponded to the inclusion criteria for meta-analysis. These studies involved the total number of 481 LPE men and 466 health control men subjects. Odds ratio (OR) and 95% confidence intervals (CIs) were used to evaluate this relationship. RESULTS: In the overall analysis, significant associations between LPE risk and 5-HTTLPR polymorphism were found (L-allele vs. S-allele OR = 0.86, 95% CI = 0.79-0.95, P = 0.002; LL vs. SS: OR = 0.80, 95% CI = 0.68-0.95, P = 0.009; LS vs. SS: OR = 0.85, 95% CI = 0.76-0.97, P = 0.012 and LL+LS vs. SS: OR = 0.88, 95% CI = 0.81-0.95, P = 0.002). Moreover, in subgroup analysis based on ethnicity, similar significant associations were detected. The Egger's test did not reveal presence of a publication bias. CONCLUSIONS: Our investigations demonstrate that 5-HTTLPR (L>S) polymorphism might protect men against LPE risk. Further studies based on larger sample size and gene-environment interactions should be conducted the role of 5-HTTLPR polymorphism and LPE risk.